Learning Styles in English Subjects and Students’ Academic Performance at Sultan Kudarat State University - Rebugio, Mae D.; Kalido, Sittie Shairah M.; Hunas, Mark Erwin S.; Llamo, Efren John I.; Alido, Rustom C.; Marata, Wan Lee B. (Randwick International of Education and Linguistics Science Journal, 2025)
Understanding different learning styles in education is critical for effective teaching and personalized learning, given their significant influence on academic performance. A misalignment between students’ preferences and instructional methods, particularly in English subjects, can impede comprehension and contribute to academic decline. This study investigated the relationship between learning styles in English subjects and academic performance among students at Sultan Kudarat State University. Specifically, it aimed to identify the predominant learning styles and academic performance of 2nd year BSED English students and assessed how they impacted academic outcomes. Employing a descriptive-correlational approach, the study involved total enumeration sampling of 2nd year English significant students. It utilized statistical measures such as frequency, percentage, mean, standard deviation, and chi-square for data analysis. Findings revealed that students’ most dominant learning styles were visual in perceptual and individual in social learning. Some students exhibited a combination of visual with group or auditory learning, suggesting adaptability to various teaching methods. Despite commendable academic performance, no significant correlation was found between dominant learning styles and academic achievement. These results may advance current knowledge on the various ways that students choose to study English and emphasize the value of individualized instruction and assistance to meet each student’s specific learning requirements.